2015
DOI: 10.1111/1745-5871.12160
|View full text |Cite
|
Sign up to set email alerts
|

Catch 22: wetlands protection and fishing for survival

Abstract: Environmental regulation of biodiversity hotspots, including wetlands, is of increasing importance in an era when species and habitat loss is common. A number of global environmental protection regimes attempt to set up processes that protect vulnerable species and their habitats. One such regulatory regime, the Ramsar Convention (Convention on Wetlands of International Importance, especially as Waterfowl Habitat), provides overarching protection for hundreds of wetlands around the world. In this paper, one Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 24 publications
0
30
0
Order By: Relevance
“…Personal communication revealed that patrolling conservation areas was indeed a great challenge for fishers, as conflict with illegal fishers could quickly become violent. Moreover, enforcing laws that prohibit or restrict fishers from fishing may not be the most plausible solution as this may affect local livelihoods, reduce food and income and create an even greater burden for already marginalised groups (Gillespie, : 343).…”
Section: Discussionmentioning
confidence: 99%
“…Personal communication revealed that patrolling conservation areas was indeed a great challenge for fishers, as conflict with illegal fishers could quickly become violent. Moreover, enforcing laws that prohibit or restrict fishers from fishing may not be the most plausible solution as this may affect local livelihoods, reduce food and income and create an even greater burden for already marginalised groups (Gillespie, : 343).…”
Section: Discussionmentioning
confidence: 99%
“…Sometimes these legal practices are contradictory, and create local spatial conflicts. Analysing both formal state law and non-state normative orders relating to the wetlands of Tonle Sap in central Cambodia, Gillespie discloses the contradictions between state-based rules on wetland protection and social norms which challenge the power of local villages adjacent to the protected area (Gillespie, 2016b(Gillespie, , 2018.…”
Section: Commodification and The Legal Geography Of Naturementioning
confidence: 99%
“…Bartel and Graham's 'Property and Place Attachment (2015) applies Nicole Graham's (2011) influential de-physicalization thesis to the legal reform process concerning biodiversity in New South Wales. As Gillespie (2015aGillespie ( , 2015b has argued in the context of Cambodia, Bartel and Graham note that 'The relevance of the dephysicalized nature of property to the protection of biodiversity is that legal and cultural discourses are unconcerned with the specific aspects of particular places. The placelessness of property creates substantial challenges for environmental laws that regulate the material aspects of landownership' (p. 8).…”
Section: Physical and Other-than-human Worldsmentioning
confidence: 99%